Ecotourism and environmental conservation in small islands in the east coast of peninsular Malaysia - Chan, Ngai Weng (Environmental Management Society, Malaysia, 2009)
Many small islands off the east coast of Peninsular Malaysia have become wellknown destinations both to foreign as well as local tourists. However, as tourism authorities, hotels and tour operators increasingly focus on mass tourism and economics, environmental degradation and other issues are affecting tourism negatively. In recent decades, Malaysia has realised the need for protection of environmental attractions and has embarked on many conservation programmes, but most of them are ad hoc and not sustained. This article examines how tourists perceive environmental conservation, willingness to pay, reasons for coming, length of stay, favourite destinations, favourite activities, etc. The results of questionnaire interviews show that small islands off the east coast of Peninsular Malaysia are currently facing serious environmental degradation, with little or no comprehensive conservation, poor enforcement, with no clearcut vision from the authorities as to their future. The study shows that there is a need for a well-planned vision of development for the small islands and stricter control from the authorities. Without better control and implementation of a vision of sustainable development, it is envisaged that these small islands will continue to deteriorate and lose their glamour and attractions gradually. They need to be conserved and stay competitive to survive, given the competition from islands in neighbouring countries